Uncovering Adrenal Incidentalomas – the role of imaging methods in diagnostic process - Matuszek, Małgorzata; Woźniak, Magdalena; Biłat, Wiktor (Journal of Education, Health and Sport, 2024)
Introduction and purpose An adrenal incidentaloma is any lesion found unexpectedly during an imaging study performed for an unrelated reason. The detection rate of incidental adrenal tumors is steadily increasing. The clinical presentation of these tumors is influenced by the specific hormones production, which are determined by their origin. Most lesions are hormonally inactive and may go undetected by physicians, although some can be malignant. The aim of this work is to summarize the utility of different imaging modalities in clinical practice. State of knowledge All adrenal incidentalomas have to undergo an imaging procedure to determine if the mass is homogeneous and lipid-rich and therefore benign or if there are some malignant features. Noncontrast computed tomography is the primary imaging technique used to evaluate adrenal lesions based on their size, structure, and density. It is worth remembering that density <10 HU and homogenous appearance is consistent with a benign adrenal mass and no further imaging is required. When additional diagnostic clarification is needed, especially in malignancy suspicion, magnetic resonance imaging with a chemical shift technique should be conducted and it may be followed by nuclear medicine methods. Conclusions Imaging methods play crucial role in diagnostic process. Imaging studies provide easy follow-ups and allow to avoid unnecessary adrenalectomies and its complications. Therefore, they contribute to optimizing patients’ health management.